Split-antecedent relative clauses and the symmetry of predicates - Poschmann, Claudia; Bargmann, Sascha; Götze, Christopher; Holler, Anke; Sailer, Manfred; Webelhuth, Gert; Zimmermann, Thomas Ede (Proceedings of Sinn und Bedeutung, 2019)
This paper presents the results of two experiments in German testing the acceptability of (non-) restrictive relative clauses (NRCs/RRCs) with split antecedents (SpAs). According to Moltmann (1992), SpAs are only grammatical if their parts occur within the conjuncts of a coordinate structure and if they have identical grammatical functions. Non-conjoined SpAs that form the subject and the object of a transitive verb are predicted to be ungrammatical. Our study shows that the acceptability of such examples improves significantly if the predicate that relates the parts of the SpA is symmetric. Moreover, it suggests that NRCs and RRCs behave differently in these cases with respect to the SpA-construal. We can make sense of this observation if we follow Winter (2016) in assuming that transitive symmetric predicates have to be analyzed as unary collective predicates and thus provide a collective antecedent for the RC at the semantic (not the syntactic) level. As we will argue, this accounts for some of the disagreement we found in the literature and gives us new insights into both the semantics of symmetric predicates and the semantics of NRCs.